Factors associated with non-adherence to angiotensin-converting enzyme inhibitors and angiotensin receptor blockers in older patients with peripheral arterial disease - Wawruch, Martin; Petrova, Miriam; Tesar, Tomas; Murin, Jan; Schnorrerova, Patricia; Paduchova, Martina; Celovska, Denisa; Havelkova, Beata; Trnka, Michal; Alfian, Sofa D.; Aarnio, Emma (Frontiers in Pharmacology, 2023)
As in other chronic conditions, medication adherence is important in the treatment of peripheral arterial disease (PAD). Our study aimed at a) analysing non-adherence to angiotensinconverting enzyme inhibitors (ACEIs) and angiotensin-receptor blockers (ARBs) in groups of older ACEI and ARB users with PAD, and b) identifying characteristics associated with non-adherence.We focused on the implementation phase of adherence (i.e., after treatment initiation and before possible discontinuation of treatment). The study cohort included ACEI/ARB users aged ≥65 years in whom PAD was newly diagnosed during 2012. Non-adherence was defined as Proportion of Days Covered (PDC)<80%.Results: Among 7,080 ACEI/ARB users (6,578 ACEI and 502 ARB users), there was no significant difference in the overall proportion of non-adherent patients between ACEI and ARB users (13.9% and 15.3%, respectively). There were differences in factors associated with non-adherence between the groups of persistent and non-persistent (i.e., discontinued treatment at some point during followup) ACEI and ARB users. Increasing age, dementia and bronchial asthma were associated with nonadherence in persistent ACEI users. General practitioner as index prescriber was associated with adherence in the groups of non-persistent ACEI users and persistent ARB users.Identified factors associated with non-adherence may help in determining the groups of patients who require increased attention.